2012
DOI: 10.1111/j.1600-6143.2012.04272.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Living and Deceased Donor Liver Transplant Recipients With Hepatocellular Carcinoma: Results of the A2ALL Cohort

Abstract: Hepatocellular carcinoma (HCC) represents an increasing fraction of liver transplant indications; the role of living donor liver transplant (LDLT) remains unclear. Recurrence and post-transplant mortality rates were compared in LDLT and deceased donor liver transplant (DDLT) patients with at least one potential living donor evaluated. HCC recurrence and post-transplant mortality were evaluated among 100 LDLT and 97 DDLT recipients in the Adult-to-Adult Living Donor Liver Transplantation Cohort Study. Mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 32 publications
11
94
1
Order By: Relevance
“…They suggested that the physiology of the small graft may stimulate tumor recurrence. The results of the A2ALL cohort in USA (20) demonstrated an impaired outcome in LDLT recipients, in which HCC recurrence remained significantly different between LDLT and DDLT after adjustment for tumor characteristics. They concluded that the higher recurrence observed after LDLT UNOS, United Network for Organ Sharing was likely due to differences in the tumor characteristics, pretransplant HCC management, and waiting time between the programs.…”
Section: Studies Comparing Ldlt and Ddlt For Hcc Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the physiology of the small graft may stimulate tumor recurrence. The results of the A2ALL cohort in USA (20) demonstrated an impaired outcome in LDLT recipients, in which HCC recurrence remained significantly different between LDLT and DDLT after adjustment for tumor characteristics. They concluded that the higher recurrence observed after LDLT UNOS, United Network for Organ Sharing was likely due to differences in the tumor characteristics, pretransplant HCC management, and waiting time between the programs.…”
Section: Studies Comparing Ldlt and Ddlt For Hcc Patientsmentioning
confidence: 99%
“…There were ten single-institutional reports (3,10,13-15, 17-19,21,22) and three multi-center reports (16,20,23).…”
Section: Studies Comparing Ldlt and Ddlt For Hcc Patientsmentioning
confidence: 99%
“…Although the differences did not reach statistical significance, HCCs in the LDLT group were more likely to have vascular invasion (22% vs. 10%) and include more poorly differentiated tumors (15% vs. 3%) than the DDLT group. In 2012, after accumulation of a significant number of cases, Kullik et al (16) reported updated data on 197 cases (100 LDLT and 97 DDLT). According to this report, the 5-year recurrence rate was significantly higher after LDLT than DDLT, as in their previous report (38% vs. 11%, P=0.0004).…”
Section: Comparative Studies Of Ldlt Vs Ddlt For Patients With Hccmentioning
confidence: 99%
“…Therefore, LDLT for patients with HCC is being accepted worldwide as a solution to donor shortage and waiting list mortality (11,12). However, with the accumulation of cases, higher recurrence rates after LDLT in comparison to DDLT have been reported by several authors (13)(14)(15)(16)(17). In this review, we aim to present a current overview of the outcomes of LDLT compared to those of DDLT in patients with HCC, with emphasis on the recurrence of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…(14) The short waiting time for transplant and excellent graft function are key arguments for living related donors in HCC patients, even though there may be a higher rate of HCC recurrence. (15) In Germany, there is no strict age limit for LT. However, most centers will only accept exceptionally patients above the age of 70 years for LT due to the organ shortage.…”
Section: Referral and Assessment For Transplantation: Selection And Amentioning
confidence: 99%